Fetal cardiac ventricular volume, cardiac output, and ejection fraction determined with four-dimensional ultrasound using Spatio-Temporal Image Correlation (STIC) and Virtual Organ Computed-aided AnaLysis (VOCAL™) - Hamill, Neil (2011)
OBJECTIVE: To quantify fetal cardiovascular parameters with Spatio-Temporal Image Correlation (STIC) and Virtual Organ Computed-aided AnaLysis (VOCAL™) utilizing the sub-feature: “Contour Finder: Trace”. STUDY DESIGN: A cross-sectional study was designed consisting of patients with normal pregnancies between 19 and 40 weeks of gestation. After STIC datasets were acquired, analysis was performed offline (4DView) and the following cardiovascular parameters were evaluated: ventricular volume in end systole and end diastole, stroke volume, cardiac output, and ejection fraction. To account for fetal size, cardiac output was also expressed as a function of head circumference, abdominal circumference, or femoral diaphysis length. Regression models were fitted for each cardiovascular parameter to assess the effect of gestational age and paired comparisons were made between the left and right ventricles. RESULTS: 1) Two hundred and seventeen patients were retrospectively identified, of whom 184 had adequate STIC datasets (85% acceptance); 2) ventricular volume, stroke volume, cardiac output, and adjusted cardiac output increased with gestational age; whereas, the ejection fraction decreased as gestation advanced; 3) the right ventricle was larger than the left in both systole (Right: 0.50 ml, IQR: 0.2 – 0.9; vs. Left: 0.27 ml, IQR: 0.1 – 0.5; p<0.001) and diastole (Right: 1.20 ml, IQR: 0.7 – 2.2; vs. Left: 1.03 ml, IQR: 0.5 – 1.7; p<0.001); 4) there were no differences between the left and right ventricle with respect to stroke volume, cardiac output, or adjusted cardiac output; and 5) the left ventricular ejection fraction was greater than the right (Left: 72.2%, IQR: 64 – 78; vs. Right: 62.4%, IQR: 56 – 69; p<0.001). CONCLUSION: Fetal echocardiography, utilizing STIC and VOCAL™ with the sub-feature: “Contour Finder: Trace”, allows assessment of fetal cardiovascular parameters. Normal fetal cardiovascular physiology is characterized by ventricular volumes that are larger on the right and ejection fractions that are greater for the left ventricle resulting in similar left and right ventricular stroke volume and cardiac output.